Performance Nutrition for Physician Trainees Working Overnight Shifts: A Randomized Controlled Trial. (18th February 2022) - Makowski, Maryam S.; Trockel, Mickey T.; Menon, Nikitha K.; Wang, Hanhan; Katznelson, Laurence; Shanafelt, Tait D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: To compare acute effects of 2 dietary interventions with usual dietary habits on physician trainees' alertness during overnight shifts. Method: This registered, controlled, block randomized crossover trial (NCT03698123) was conducted between October 2018 and May 2019 at Stanford Medicine. Physician trainees working at least 3 overnight shifts during a 1-week period were recruited. During the first night, participants followed their usual dietary habits. During the intervention nights (low carbohydrate-to-protein ratio and high carbohydrate-to-protein ratio interventions), participants received healthy dinners, snacks, water, and, upon request, caffeinated beverages, at the beginning of their shifts and were instructed to eat meals before 10 pm . The sequence of interventions on the second and third nights were block randomized across study weeks. Outcome measures (a priori) were overnight changes in validated measures of specific neurobehavioral dimensions: psychomotor vigilance, sensory–motor speed, working memory, and risk decision making, as well as self-reported sleepiness and work exhaustion. Results: Sixty-one physician trainees participated in this study. Compared with usual dietary habits, overnight changes in psychomotor vigilance scores (scale 0–1, 000) improved by 51.02 points (95% CI: 12.08, 89.96) and sleepiness (scale 1–7) improved by 0.69 points (95% CI: 0.33, 1.05) under the low carbohydrate-to-protein ratio intervention. Compared with usual dietary habits, overnight changes in sleepiness (scale 1–7) improved by 0.61 points (95% CI: 0.25, 0.96) under the high carbohydrate-to-protein ratio intervention. Neither intervention had beneficial effects relative to usual dietary habits with respect to sensory–motor speed, working memory, risk decision making, or work exhaustion. There were no differences in outcomes between low carbohydrate-to-protein ratio and high carbohydrate-to-protein ratio interventions. Conclusions: Dietary interventions may mitigate negative effects of physician trainee sleep deprivation during overnight shifts. Future studies are warranted to further examine the effectiveness of nutritional strategies on physician alertness during overnight shifts.